Overlapping CRE and E Box Motifs in the Enhancer Sequences of the Bovine Leukemia Virus 5′ Long Terminal Repeat Are Critical for Basal and Acetylation-Dependent Transcriptional Activity of the Viral Promoter: Implications for Viral Latency - Calomme, Claire (American Society for Microbiology, 2004)
Bovine leukemia virus (BLV) infection is characterized by viral latency in a large proportion of cells containing an integrated provirus. In this study, we postulated that mechanisms directing the recruitment of deacetylases to the BLV 5′ long terminal repeat (LTR) could explain the transcriptional repression of viral expression in vivo. Accordingly, we showed that BLV promoter activity was induced by several deacetylase inhibitors (such as trichostatin A [TSA]) in the context of episomal LTR constructs and in the context of an integrated BLV provirus. Moreover, treatment of BLV-infected cells with TSA increased H4 acetylation at the viral promoter, showing a close correlation between the level of histone acetylation and transcriptional activation of the BLV LTR. Among the known cis-regulatory DNA elements located in the 5′ LTR, three E box motifs overlapping cyclic AMP responsive elements (CREs) in U3 were shown to be involved in transcriptional repression of BLV basal gene expression. Importantly, the combined mutations of these three E box motifs markedly reduced the inducibility of the BLV promoter by TSA. E boxes are susceptible to recognition by transcriptional repressors such as Max-Mad-mSin3 complexes that repress transcription by recruiting deacetylases. However, our in vitro binding studies failed to reveal the presence of Mad-Max proteins in the BLV LTR E box-specific complexes. Remarkably, TSA increased the occupancy of the CREs by CREB/ATF. Therefore, we postulated that the E box-specific complexes exerted their negative cooperative effect on BLV transcription by steric hindrance with the activators CREB/ATF and/or their transcriptional coactivators possessing acetyltransferase activities. Our results thus suggest that the overlapping CRE and E box elements in the BLV LTR were selected during evolution as a novel strategy for BLV to allow better silencing of viral transcription and to escape from the host immune response.